2019
DOI: 10.7821/naer.2019.1.344
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Professional Competences of Last Year’s Students of Pre-Primary Education and Primary Education Degrees and Students of Training Teachers Master

Abstract: This research aims to obtain knowledge of the perception of last year´s students’ in Pre-primary and Primary Education Degrees and Secondary Education, Vocational Education and Languages Education in Teachers University Master (better known as Training Teachers Master or Secondary Education Master) at Jaen University (UJA) and the National Distance Education University (UNED), about the most important competences in their learning process. Those competences allow students to develop their knowledge and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Along with these initiatives, the support, certification, and recognition of the public administrations will be in only the early stages and will require systematic, previous, and continuous analysis of the education plans [47].…”
Section: Discussionmentioning
confidence: 99%
“…Along with these initiatives, the support, certification, and recognition of the public administrations will be in only the early stages and will require systematic, previous, and continuous analysis of the education plans [47].…”
Section: Discussionmentioning
confidence: 99%
“…The difference obtained in the data on perceived stress between men and women may be conditioned by the current situation due to the COVID-19 pandemic and with the different ways that women and men have of facing the constant challenges of university education such as previous works corroborate. So, in the academic field, [37,38] observed that according to the student's development, the perceived stimuli may or may not be stress generators, estimating that male students presented lower levels of stress than female ones.…”
Section: Discussionmentioning
confidence: 99%
“…The difference obtained in the data on perceived stress between men and women may be conditioned by the current situation due to the COVID-19 pandemic, and with the different ways that women and men have of facing the constant challenges of university education such as previous works corroborate. So, in the academic field, [32][33] observed that according to the student's development, the perceived stimuli may or may not be stress generators, estimating that male students presented lower levels of stress than female ones.…”
Section: Discussionmentioning
confidence: 99%